(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In the article , the equations of motion and the trajectory of movement of a piece of cotton in the pipeline of a pneumotransport device are analyzed, in which the laws of the change of the movement of a piece of cotton under the influence of aerodynamic resistance, weight, inertia, impact and reaction forces are derived, and the change of quality indicators of cotton during movement is theoretically based .